2014
DOI: 10.1002/dta.1642
|View full text |Cite
|
Sign up to set email alerts
|

Targeting misuse of 2‐amino‐N‐ethyl‐1‐phenylbutane in urine samples: in vitro–in vivo correlation of metabolic profiles and development of LC‐TOF‐MS method

Abstract: A phenyethylamine derivative, 2-amino-N-ethyl-1-phenylbutane (2-AEPB), has recently been detected in doping control and drugs-of-abuse samples, and identified as a non-labelled ingredient in a dietary supplement. To facilitate efficient control of this substance we have studied the in vitro metabolic behaviour of 2-AEPB with human liver preparation, compared these results with in vivo pathways in human, and finally propose an analytical strategy to target the potential misuse of 2-AEPB for toxicological, foren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The routinely applied GC‐MS‐based test method was assessed concerning its LOD for NN‐DMPPA, which was determined at 30 ng/mL and, thus, fulfilling WADA MRPL criteria. Similarly, Kobayashi et al . and Wojtowicz et al .…”
Section: Stimulantsmentioning
confidence: 61%
See 2 more Smart Citations
“…The routinely applied GC‐MS‐based test method was assessed concerning its LOD for NN‐DMPPA, which was determined at 30 ng/mL and, thus, fulfilling WADA MRPL criteria. Similarly, Kobayashi et al . and Wojtowicz et al .…”
Section: Stimulantsmentioning
confidence: 61%
“…[203] The routinely applied GC-MS-based test method was assessed concerning its LOD for NN-DMPPA, which was determined at 30 ng/mL and, thus, fulfilling WADA MRPL criteria. Similarly, Kobayashi et al [204] and Wojtowicz et al [205] investigated options to detect the newly identified phenethylamine derivative 2-amino-N-ethyl-1-phenylbutane (2-AEPB) in doping controls. Following in vitro and in vivo studies, the intact compound and its desethylated analogue were identified as appropriate target analytes, enabling the unequivocal detection of the prohibited substance down to approximately 3-5 ng/mL using both LC-HRMS and GC-MS.…”
Section: Stimulantsmentioning
confidence: 99%
See 1 more Smart Citation